Media Narratives and Social Exclusion: A Structuration Analysis of Rohingya Refugee Coverage in Indonesia - Krida, Graha Wira; Rusadi, Udi (Yayasan Sinergi Kawula Muda, 2025)
This study examines the role of the media in shaping public meaning towards Rohingya refugees in Indonesia through Anthony Giddens' structuration theory. The problem discussed is how the media constructs narratives that are in line with the political and economic interests of the elite, which directly shape the public's meaning towards refugees as a